Evidence of Borrelia theileri in Wild and Domestic Animals in the Kafue Ecosystem of Zambia - Qiu, Yongjin; Squarre, David; Nakamura, Yukiko; Lau, Alice C. C.; Moonga, Lavel Chinyama; Kawai, Naoko; Ohnuma, Aiko; Hayashida, Kyoko; Nakao, Ryo; Yamagishi, Junya; Sawa, Hirofumi; Namangala, Boniface; et al. (Microorganisms (Basel), 2021)
Members of the genus Borrelia are arthropod-borne spirochetes that are human and animal pathogens. Vertebrate hosts, including wild animals, are pivotal to the circulation and maintenance of Borrelia spirochetes. However, information on Borrelia spirochetes in vertebrate hosts in Zambia is limited. Thus, we aimed to investigate the presence of Borrelia spirochetes in wild animals and cattle in Zambia. A total of 140 wild animals of four species and 488 cattle DNA samples from /near the Kafue National Park were collected for real-time PCR screening, followed by characterization using three different genes with positive samples. Five impalas and 20 cattle tested positive using real-time PCR, and sequence analysis revealed that the detected Borrelia were identified to be Borrelia theileri, a causative agent of bovine borreliosis. This is the first evidence of Borrelia theileri in African wildlife and cattle in Zambia. Our results suggest that clinical differentiation between bovine borreliosis and other bovine diseases endemic in Zambia is required for better treatment and control measures. As this study only included wild and domestic animals in the Kafue ecosystem, further investigations in other areas and with more wildlife and livestock species are needed to clarify a comprehensive epidemiological status of Borrelia theileri in Zambia.